Grupo Etnico - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a un grupo de varios indigenas entre hombres, mujers y bebés y niños posanado ante la camara, no se sabe a cual grupo etnico pertenecen.
ENGLISH: A group of several indigenous people, including men, women, babies and children, was observed posing in front of the camera; it is not known which ethnic group they belong to.

SPANISH: Se observó a un grupo de varios indigenas entre hombres, mujers y bebés y niños posanado ante la camara, no se sabe a cual grupo etnico pertenecen.
ENGLISH: A group of several indigenous people, including men, women, babies and children, was observed posing in front of the camera; it is not known which ethnic group they belong to.
Ethnic group
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Amazonian Faces|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Rostros Amazonicos|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Amazonian Faces